(untitled) (American Journal of Islam and Society, 2003)
The Thirty-second Annual AMSS Conference, cosponsored this year by Indiana University’s Middle Eastern and Islamic Studies program and the department of Near Eastern Languages and Cultures, analyzed "East Meets West: Understanding the Muslim Presence in Europe and North America." Katherine Bullock (program committee chair, University of Toronto), Nazif Shahrani (professor of anthropology, director of Middle Eastern and Islamic studies program, Indiana University), Patrick O’Meara (dean, International Programs, Indiana University), and Louay Safi (president, AMSS) welcomed attendees and made introductory remarks. Since the passing of Edward Said coincided with the beginning of the conference, in his welcoming remarks Shahrani referred to this great scholar’s lasting legacy. In fact, many panelists during the course of the conference talked about the importance of Said’s research to their own work. Regular AMSS attendees such as myself would tell you that this conference was a tightly organized orchestra of excellent sessions, one after the other. The number of sessions was smaller than usual, and there were fewer parallel sessions, probably because far more academic rigor had been exercised in selectiong papers than had been the case in previous conferences. A special delight on the first day was the lunch and jumu’ah prayer at the Bloomington Islamic Center, catered and served by Bloomington Muslim community volunteers. After these events, the conference began in earnest. The opening panel, "A Political Philosophical Perspective on Islam and Democracy," featured M. A. Muqtedar Khan (Adrian College), who addressed the theoretical aspects of this debate, and Nazia Khandwalla (University of Texas), who looked at the debate in an empirical study of slum-dwelling women in Karachi ...